2019
DOI: 10.1634/theoncologist.2019-0300
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Response to Neoadjuvant Chemotherapy and the Molecular Classification of Locally Advanced Breast Cancer in a Latin American Cohort

Abstract: Background. The majority of patients with breast cancer in Colombia are admitted into oncological centers at locally advanced stages of the disease (53.9%). The aim of this study was to describe the pathological response obtained with neoadjuvant chemotherapy (NACT) according to the molecular classification of breast cancer in patients with locally advanced tumors treated within the National Cancer Institute (NCI) Functional Breast Cancer Unit (FBCU) in Bogotá, Colombia. Materials and Methods. This was an obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
1
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 29 publications
4
11
1
8
Order By: Relevance
“…24,25 Luminal breast cancer subtype had lower response to NAC when compare to other subtypes. 26,27 Although there were higher proportion of T4 breast cancer recruited in this current study, the rate of pCR in the current study was similar to the recent report of clinically node-positive breast cancer receiving NAC. 25 However, approximately 70% of the patients received neoadjuvant AC regimen which resulted in lower response when compare to the addition of taxane-based regimen.…”
Section: Discussionsupporting
confidence: 86%
“…24,25 Luminal breast cancer subtype had lower response to NAC when compare to other subtypes. 26,27 Although there were higher proportion of T4 breast cancer recruited in this current study, the rate of pCR in the current study was similar to the recent report of clinically node-positive breast cancer receiving NAC. 25 However, approximately 70% of the patients received neoadjuvant AC regimen which resulted in lower response when compare to the addition of taxane-based regimen.…”
Section: Discussionsupporting
confidence: 86%
“…Breast cancer (BC) is currently the most common malignancy in women, both in developed and less developed countries, and the leading cause of cancer-related deaths among women worldwide, with a high incidence rate [ 1 , 2 ]. Every breast cancer subtype is characterized by intrinsic molecular features and metastatic lesions, and their natural heterogeneity leads to a high diversity in prognosis and clinical responses to available medical treatments, even for patients with similar diagnosis, histology and stage of disease [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…HR-positive patients have relatively more favorable outcome, although they are less responsive to NACT than TNBC and HER2 + tumors [82]. Indeed, it is widely accepted that patients with TNBC and HER2-enriched tumor showed higher pCR rates than luminal subtype [83848586]. Prat et al [83] evaluated the recurrence risk based on BC subtype and confirmed the independent predictive and prognostic value of intrinsic subtype at diagnosis for patients after NACT.…”
Section: Hr Her2 and Intrinsic Molecular Subtypesmentioning
confidence: 99%
“…The correlation between pCR and survival is significant in partial patients based on molecular subtypes. Díaz-Casas et al [84] reported longer EFS and OS in patients who achieved pCR, which was statistically significant only in patients with TNBC. In a study involving 13,939 patients, pCR was demonstrated to be significantly associated with 5-year OS in patients with luminal B, HER2 + , and TNBC (93.0%, 94.2%, and 90.6%, respectively, HER2 + vs. TNBC, p = 0.016) [87].…”
Section: Hr Her2 and Intrinsic Molecular Subtypesmentioning
confidence: 99%